Team leadership and patient outcomes in US psychiatric treatment settings - Wells, Rebecca; Jinnett, Kimberly; Alexander, Jeffrey; Lichtenstein, Richard; Liu, Dawei; Zazzali, James L. (Social science & medicine (1982), 2006)
Previous studies suggest that psychiatric patients mirror the behaviors of the staff members who treat them, but there is little empirical evidence about how staff dynamics affect patients over time. The goals of this study were to examine associations between: (1) team leader discipline and mutual respect among treatment team members; and (2) mutual respect among team members and improvements in patient quality of life. Two models were tested on data from psychiatric treatment teams within the US Veterans Administration. The first examined associations between the discipline of each team's emergent leader and the level of mutual respect among that team's members. The second model tested associations between mutual respect among staff and changes over time in patients’ quality of life. The subjects for model 1 were psychiatric staff members ( n = 785 ) whose responses were aggregated for team-level analyses ( n = 78 ). Mutual respect was highest in social worker-led teams and lowest in physician-led teams. The subjects for model 2 were 1638 seriously mentally ill patients in 44 of the units examined in the first model. When mutual respect among staff was greater, patients improved more over time in their satisfaction with the quality of their housing, relations with families, social life, and finances. Together, these analyses imply that mutual respect may improve patient outcomes and that leadership by some disciplines may facilitate such dynamics. In general, leaders may consider learning from other disciplines’ strengths to improve their impact.